2018
DOI: 10.1038/s41467-018-07913-4
|View full text |Cite
|
Sign up to set email alerts
|

Genomic effects of population collapse in a critically endangered ironwood tree Ostrya rehderiana

Abstract: Increased human activity and climate change are driving numerous tree species to endangered status, and in the worst cases extinction. Here we examine the genomic signatures of the critically endangered ironwood tree Ostrya rehderiana and its widespread congener O. chinensis. Both species have similar demographic histories prior to the Last Glacial Maximum (LGM); however, the effective population size of O. rehderiana continued to decrease through the last 10,000 years, whereas O. chinensis recovered to Pre-LG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 63 publications
5
76
0
Order By: Relevance
“…To prevent biases in SNP calling accuracy due to the difference of samples size between groups, single-sample SNP and genotype calling were first implemented using GATK (DePristo et al , 2011) with ‘HaplotypeCaller’, and then multi-sample SNPs were identified after merging the results of each individual by ‘GenotypeGVCFs’. A series of filtering steps were performed to reduce false positives (Yang et al , 2018), including removal of (1) indels with a quality scores < 30, (2) SNPs with more than two alleles, (3) SNPs at or within 5 bp from any indels, (4) SNPs with a genotyping quality scores (GQ) < 10, and (5) SNPs with extremely low (< one-third average depth) or extremely high (> threefold average depth) coverage. The identified SNPs were used for subsequent GWAS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…To prevent biases in SNP calling accuracy due to the difference of samples size between groups, single-sample SNP and genotype calling were first implemented using GATK (DePristo et al , 2011) with ‘HaplotypeCaller’, and then multi-sample SNPs were identified after merging the results of each individual by ‘GenotypeGVCFs’. A series of filtering steps were performed to reduce false positives (Yang et al , 2018), including removal of (1) indels with a quality scores < 30, (2) SNPs with more than two alleles, (3) SNPs at or within 5 bp from any indels, (4) SNPs with a genotyping quality scores (GQ) < 10, and (5) SNPs with extremely low (< one-third average depth) or extremely high (> threefold average depth) coverage. The identified SNPs were used for subsequent GWAS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Habitat destruction caused by changing climate and human activities has driven 59 numerous plant species to endangered status (Yang et al, 2018). Recently there has 60 been a push to establish natural reserves to reduce the chance of extinction in 61 vulnerable species.…”
Section: Introductionmentioning
confidence: 99%
“…SMC approaches, that are typically implemented using a hidden Markov model, have provided invaluable insights into changes in population size through time in various taxonomic groups. For instance, using phased genome sequences, Yang et al [42] provided evidence for continuous decline in the critically endangered population of ironwood tree (Ostrya rehderiana), accompanied by an increased number of deleterious mutations. However, some SMC-based methods make several assumptions, including the absence of population structure, migration, or admixture, which may bias inferences [43,44].…”
Section: Spatiotemporal Inference In Metapopulationsmentioning
confidence: 99%
“…However, some SMC-based methods make several assumptions, including the absence of population structure, migration, or admixture, which may bias inferences [43,44]. To circumvent those limitations, the most recent extensions of SMC-based methods, including the multiple sequential Markovian coalescent (MSMC), have the potential to handle larger sample sizes [30,41,42] as well as more complex demographic models (e.g., more than one population, asymmetric migration rates, variable N e along the genome, etc.) [26], without necessarily needing phased data [45].…”
Section: Spatiotemporal Inference In Metapopulationsmentioning
confidence: 99%